A THIN, HARDWARE-SUPPORTED MIDDLEWARE MANAGEMENT SYSTEM FOR RECONFIGURABLE MANUFACTURING SYSTEMS - McLean, Roscoe Roy Peter; Padayachee, Jared; Bright, Glen (The South African Journal of Industrial Engineering, 2015)
The reconfigurable manufacturing system (RMS) paradigm was introduced in response to the need for a manufacturing environment that can handle high-frequency market-driven change. Although this has resulted in much research into the implementation of such a system, there is currently a gap in the technology covering the rapid establishment of control after a reconfiguration. This gap involves the detection of the factory floor’s state, and the communication link between the factory floor and the high-level software (ERP and MES). This paper proposes a thin, hardware-supported middleware management system to support the reconfiguration process and to support industrial implementation to the RMS paradigm.